MRI findings of Persistent Mullerian Duct Syndrome: A Rare Case Report - RAMBIR SINGH; SUNIL D KUMAR; NIDHI AGGARWAL (Journal of Clinical and Diagnostic Research, 2017)
Embryologically mullerian duct derivatives lead to formation of female genitalia and wolffian duct derivatives to male genitalia. Presence of mullerian duct derivatives in a chromosomally normal male (XY) leads to male pseudohermaphroditism and is referred to as Persistent Mullerian Duct Syndrome (PMDS). A young male patient with bilateral cryptorchidism presented to our hospital who was subsequently imaged. There are many case reports of persistent mullerian duct syndrome but they focus mainly on surgical aspects. In this article, MRI features of persistent müllerian duct syndrome are presented.